2019
DOI: 10.1021/acsabm.9b00799
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reactions-Based Modified/Functionalized Materials in the Biomedical Platforms

Abstract: In various physiological and biological functions, bioactive materials as a key technique or procedure hold promise for the achievement of therapeutic effects in animals or humans. Interesting merit in the biomedical field is the emergence of a neoteric strategy for functionalization of materials. Expressly, the combination of multicomponent reactions (MCRs) with materials chemistry is the modernizaation of functionalized architectures with flexible features and opens an interesting avenue for biologically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 132 publications
0
24
0
Order By: Relevance
“…The structural resemblance of these compounds to the coenzyme reduced nicotinamide adenine dinucleotide (NADH) sparked the potential pharmaceutical properties, and till today, the Hantzsch synthesis is the main route for obtaining such products, which are eventually used as active pharmaceutical ingredients in the pharmaceutical industry [ 3 , 8 ]. An analysis of the market shows that there are over 7000 drugs derived from dihydropyridines, some of which are blockbuster drugs, such as Tamiflu ® , dioscorine, ibogaine, and isoquinuclidines [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structural resemblance of these compounds to the coenzyme reduced nicotinamide adenine dinucleotide (NADH) sparked the potential pharmaceutical properties, and till today, the Hantzsch synthesis is the main route for obtaining such products, which are eventually used as active pharmaceutical ingredients in the pharmaceutical industry [ 3 , 8 ]. An analysis of the market shows that there are over 7000 drugs derived from dihydropyridines, some of which are blockbuster drugs, such as Tamiflu ® , dioscorine, ibogaine, and isoquinuclidines [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Javanbakht et al synthesized a pH-responsive photoluminescent nanocarrier via encapsulation of graphene quantum dots by MIPs. [199] A pH-responsive MIP layer was fabricated via precipitation FRP in water media using doxorubicin, 2-hydroxyethyl methacrylate, and N,N′-methylenebisacrylamide ethylene as the template, functional monomer, and crosslinker, respectively, to form a nontoxic and biocompatible drug delivery system. In vitro drug release studies revealed that at a pH of 7.4, minimal drug leakage occurred, which could decrease harmful effects in normal tissues.…”
Section: Ph-responsive Mipsmentioning
confidence: 99%
“…Isocyanides are hubs in chemistry, having reaction plasticity yet conserved reactivities, and can function as integral members of large multimolecular assemblies, or just contribute a few atoms. The isocyanide functional group is of high relevance to different fields of science, 1 including astronomy, 2 biology, 3 information technology, 4,5 materials science, 6 and most importantly chemistry. 7 Isocyanides are isolobal to carbon monoxide and therefore there is a rich metalorganic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…A recent bibliometric analysis using Sci-Finder revealed that isocyanides are mentioned in >21 000 publications, excluding patents. However, just 9 isocyanides (1)(2)(3)(4)(5)(6)(7)(8)(9) account for >19 000 citations (>90%) of all isocyanide research papers. These reoccurring isocyanides are the commercially available tert-butyl 1, cyclohexyl isocyanide 2, TOSMIC 3, isocyanoaceticacid esters 4 and 9, 2,6-dimethyl phenyl 5, benzyl 6, methyl 7 and phenyl isocyanide 8.…”
Section: Introductionmentioning
confidence: 99%